Cosmic-ray capabilities of the ARIANNA neutrino experiment - Nelles, Anna (Proceedings of Science, 2017)
The ARIANNA experiment is designed to measure the radio emission created by neutrinos interacting in the Antarctic ice. The detection is achieved by installing high gain log-periodic dipole antennas just below the surface, which will record the radio pulses. The current design foresees more than 1000 independent radio detection stations with a spacing of at least a kilometer. The ARIANNA design also includes upward facing antennas to reject radio signals from air showers. These rejection capabilities in turn make ARIANNA a very efficient cosmic ray detector. The bandwidth of 50 - 1000 MHz is wider than those of most dedicated air shower arrays and the extremely radio-quiet environment on the Ross Ice Shelf allows for the detection of cosmic rays based purely on a self-trigger. We will report on the cosmic ray detection conducted with the pilot-stage array. We will discuss self-trigger efficiency and event reconstruction including arrival directions, energy and flux measurements. These measurements illustrates that air shower signals are an excellent calibration tool for neutrino measurements and to monitor detector operations.
CRIS-Team Scopus Importer:2023-08-15